Editorial: Strategies in tissue engineering and regenerative medicine. Issue 3 (4th March 2013) - Schenke‐Layland, Katja; Walles, Heike
<x xml:space="preserve">Abstract</x> "Strategies in Tissue Engineering": this special issue is edited by Prof. Katja Schenke‐Layland and Prof. Heike Walles and covers many salient aspects of tissue engineering and regenerative medicine. The issue includes articles on Raman spectroscopy and its application in tissue engineering; bioreactor design and surface functionalization for tissue culture applications; improved method for RNA isolation from tissue samples and much more. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>